Luteolin Prevents Cardiac Dysfunction and Improves the Chemotherapeutic Efficacy of Doxorubicin in Breast Cancer - Shi, Youyang; Li, Feifei; Shen, Man; Sun, Chenpin; Hao, Wei; Wu, Chunyu; Xie, Ying; Zhang, Shuai; Gao, Hongzhi; Yang, Jianfeng; Zhou, Zhongyan; Gao, Dongwen; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Doxorubicin (Dox) is one of the most effective chemotherapy agents used in the treatment of solid tumors and hematological malignancies. However, it causes dose-related cardiotoxicity that may lead to heart failure in patients. Luteolin (Lut) is a common flavonoid that exists in many types of plants. It has been studied for treating various diseases such as hypertension, inflammatory disorders, and cancer. In this study, we evaluated the cardioprotective and anticancer effects of Lut on Dox-induced cardiomyopathy in vitro and in vivo to explore related mechanisms in alleviating dynamin-related protein (Drp1)-mediated mitochondrial apoptosis. Methods: MTT and LDH assay were used to determine the viability and toxicity of cardiomyocytes treated with Dox and Lut. Flow cytometry was used to examine ROS levels, and electron and confocal microscopy was employed to assess the mitochondrial morphology. The level of apoptosis was examined by Hoechst 33258 staining. The protein levels of myocardial fission protein and apoptosis-related protein were examined using Western blot. Transcriptome analysis of the protective effect of Lut against Dox-induced cardiac toxicity in myocardial cells was performed using RNA sequencing technology. The protective effects of Lut against cardiotoxicity mediated by Dox in zebrafish were quantified. The effect of Lut increase the antitumor activity of Dox in breast cancer both in vitro and in vivo were further employed. Results: Lut ameliorated Dox-induced toxicity in H9c2 and AC16 cells. The level of oxidative stress was downregulated by Lut after Dox treatment of myocardial cells. Lut effectively reduced the increased mitochondrial fission post Dox stimulation in cardiomyocytes. Apoptosis, fission protein Drp1, and Ser616 phosphorylation were also increased post Dox and reduced by Lut. In the zebrafish model, Lut significantly preserved the ventricular function of zebrafish after Dox treatment. Moreover, in the mouse model, Lut prevented Dox-induced cardiotoxicity and enhanced the cytotoxicity in triple-negative breast cancer by inhibiting proliferation and metastasis and inducing apoptosis.